Analysis of Real-Time Control Systems using First-Order Continuization - Gaukler, Maximilian (ARCH20 (EPiC Series in Computing, vol. 74), 2020)
Real-Time control systems can be difficult to analyze due to the mixture of discrete-time and continuous-time dynamics. This difficulty is particularly pronounced if the timing is non-periodic, e.g., due to network or execution effects. Still, most control loops behave similar to a purely continuous-time system disturbed by a small discretization error, which is exploited by Bak and Johnson (2015) in the method of Continuization. This paper uncovers limitations of that work and presents an extension, First-Order Continuization, based on a new formal framework that recovers previous results and eases future development.<br
Keywords: Reachability Analysis; Cyber-Physical Systems; Real-Time Systems; Digital Control; Verification; Abstraction; Hybrid Automata